Preparation and Analysis of Dual-Property Coated Metal Foams for Potential Wick Structures in Heat Pipe Applications - Bonardo, Doli; Hollanda Arief Kusuma; Muhammad Tanveer; Dharma, Budi; Amri, Fauzan (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Hydrophilic and hydrophobic coated metal foams have been successfully prepared via a cleaning procedure and a simple spraying technique to be used as a wick structure in a heat pipe. The main object of this work is to explore the effect of hydrophilic and hydrophobic layers on the metal foam and to study the properties of the metal foams. To achieve this goal, 3D-OM analyses were performed to identify the pore size of the metal foam. To observe the surface morphology and porosity of the metal foam, SEM analysis was carried out and succeeded in observing the changes in the surface roughness of the hydrophilic and hydrophobic coated metal foams. The pore diameter, porosity and density of metal foam were 633.38 µm, 48.46% and 4.62 g/cm3, respectively. FT-IR analysis was also performed with the results showing that the hydrophobic coating did not affect the overall molecular group composition. Contact angle analysis shown that the values were 74° and 112° (first day) on the hydrophilic and hydrophobic coated samples.